Comparison of TyG Index and HbA1c in Identifying Poor Glycemic Control in Type 2 Diabetes Mellitus - Muhammad Adil Ramzan, Faiza Irem, Nusrat Ullah Khan, Hassan Mahmood, Rafaqat Malik, Ifrah Zafar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) remains a major global health concern, with poor glycemic control contributing substantially to long-term vascular complications and increased healthcare burden. Glycated hemoglobin (HbA1c) is the standard biomarker for monitoring long-term glycemic status; however, its diagnostic limitations have encouraged investigation of alternative metabolic indicators. The Triglyceride-Glucose (TyG) Index has emerged as a simple surrogate marker reflecting insulin resistance and metabolic dysfunction. Objective: To compare the utility of the Triglyceride-Glucose Index and HbA1c in identifying poor glycemic control among patients with Type 2 Diabetes Mellitus. Materials and Methods: This multicenter cross-sectional comparative study was conducted from June 2022 to March 2023 at Karachi Metropolitan University/Karachi Medical and Dental College, Karachi, Pakistan, and Department of Medicine, West Medical Ward, Mayo Hospital, Lahore, Pakistan. A total of 180 diagnosed Type 2 Diabetes Mellitus patients aged 30–70 years were enrolled through non-probability consecutive sampling. Demographic characteristics, fasting plasma glucose, serum triglycerides, HbA1c, and metabolic variables were recorded. Poor glycemic control was defined as HbA1c ≥7.0%. The TyG Index was calculated using fasting plasma glucose and triglyceride levels. Statistical analysis was performed using SPSS version 26.0. Results: Among 180 participants, 104 (57.8%) were males and 76 (42.2%) were females. Patients with poor glycemic control demonstrated significantly higher TyG Index values (9.43 ± 0.55 vs 8.69 ± 0.47; p<0.001). TyG Index showed strong positive correlations with HbA1c (r=0.72, p<0.001), fasting plasma glucose (r=0.79, p<0.001), and triglyceride levels (r=0.76, p<0.001). Receiver operating characteristic analysis demonstrated TyG Index sensitivity of 84.6%, specificity of 80.9%, and AUC of 0.88 for identifying poor glycemic control. Conclusion: TyG Index demonstrated substantial diagnostic utility and strong association with poor glycemic control among Type 2 Diabetes Mellitus patients. Although HbA1c remains the primary glycemic biomarker, TyG Index may serve as an economical supplementary metabolic marker for identifying patients at increased risk of inadequate glycemic control. Keywords: Type 2 Diabetes Mellitus, TyG Index, HbA1c, Glycemic Control, Insulin Resistance